The Discursive Construction of Race as a Professional Identity Category in Two Texas Chambers of Commerce - Shrikant, Natasha (International Journal of Business Communication, 2018)
This study employs membership categorization analysis to illustrate multiple ways that race is constituted as professional identity in two chambers of commerce in a large Texas city. One of the chambers—the Asian American City Chamber of Commerce (AACC)—is explicitly defined in terms of race, while the second—the North City Chamber of Commerce (NCC)—is defined by a particular geographic area locally associated with being White. Analysis of naturally occurring talk in each organization illustrates how members of the AACC overtly discuss racial categories as professional categories. Members of the NCC avoid explicitly talking about race but do implicitly construct a White professional identity. Thus, racial identity and professional identity are constructed as inseparable identity categories in each chamber. Overall, interactions in the AACC and NCC tend to reproduce differences between “minority businesses” and “normal businesses”—understood to be White, but in which White race is invisible—thus contributing to a Texas business community in which Whiteness reigns as the dominant, invisible professional identity category.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMzI5NDg4NDE1NTk0MTU2